A review on pore-fractures in tectonically deformed coals. (15th October 2020) - Yu, Song; Bo, Jiang; Ming, Li; Chenliang, Hou; Shaochun, Xu
Highlights: The heterogeneity of fractures in TDCs was addressed. The geodynamics mechanisms for the fractures in various TDCs were proposed. The generation mechanisms for nanopores were established. Abstract: Exploitation of coalbed methane (CBM) has dual advantages of not only providing alternative clean-energy but also effectively reducing the proneness for gas outbursts. CBM reservoir properties for tectonically deformed coals (TDCs) differ significantly in comparison to neighboring primary coals, largely attributing to their pore-fracture transitions. Considerable efforts have been invested to capture the structural properties of wide scales in TDCs over the last 54 years. Here, the pore-fractures in TDCs were systematically reviewed and their geodynamic mechanisms were innovatively proposed with the recommendations and future directions finally. The classification schemes of TDCs are becoming increasing refinement with the aid from quantitative characterization of fractures and from geophysical identification as well. Analysis of high fidelity indicated the significant improvement in distributions and heterogeneities for fractures during brittle, and transitional stages, however, fractures in ductile TDCs constrain higher curvature and smaller width. The heterogeneities of seepage pores (>100 nm) decrease and those of all sub-ranges within nanopores (2–100 nm) increase with the enhancing deformation intensity based on fluid injection methods and multi-single models. The tectonic transformation could affect pores of 0.6–1.5 nm in diameter and further extend to 0.3–0.6 nm for strong brittle deformation and mylonitization process. Generally, these tectonic transformations become weaker with the decreasing geometrical scale. The fractures of weak-, and strong-deformation stage were primarily attributed to mechanisms of friction heat and strain energy respectively, however, the nanopores was macromolecular genesis. Additionally, the coupling mechanisms of thermal evolution and dynamic metamorphism still need to be further established in future.